2020
DOI: 10.3390/jcm9072231
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Patients with Unprotected Left Main Coronary Artery Disease Treated with Percutaneous Angioplasty versus Bypass Grafting: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background and Aim: Treatment of patients with left main coronary artery disease (LMCA) with percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) remains controversial. The aim of this meta-analysis was to compare the long-term clinical outcomes of patients with unprotected LMCA treated randomly by PCI or CABG. Methods: PubMed, MEDLINE, Embase, Scopus, Google Scholar, CENTRAL and ClinicalTrials.gov database searches identified five randomized trials (RCTs) including 4499 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These findings are comparable to those of another study, which reported slightly different rates for cardiac deaths, MI, and revascularization, potentially attributable to variations in sample size, demonstrating the need for further research to understand these discrepancies better (17). Another randomized trial found a lower incidence of stroke in LM PCI patients but similar rates of revascularization, supporting the safety and efficacy of PCI in this patient population (18).…”
Section: Discussionsupporting
confidence: 78%
“…These findings are comparable to those of another study, which reported slightly different rates for cardiac deaths, MI, and revascularization, potentially attributable to variations in sample size, demonstrating the need for further research to understand these discrepancies better (17). Another randomized trial found a lower incidence of stroke in LM PCI patients but similar rates of revascularization, supporting the safety and efficacy of PCI in this patient population (18).…”
Section: Discussionsupporting
confidence: 78%
“…True bifurcation disease was not associated with all-cause or cardiovascular mortality in our study. However, previous studies have demonstrated that bifurcations themselves yield risks of cardiac mortality [ 4 , 5 , 33 ] and, in our study, there was a statistically significant usage of DCBs over DESs for true bifurcational disease to tackle this anatomical challenge [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 53%
“…Traditionally, coronary artery bypass grafting (CABG) was the mainstay of treatment in patients requiring revascularisation for LMS disease and percutaneous coronary intervention (PCI), reserved only as a “salvage” option [ 2 , 3 , 4 ]. With increasing evidence supporting the use of PCI [ 2 , 5 , 6 , 7 ], this is now a recognised and guideline-indicated alternative approach [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…While it has long remained the prerogative of the surgeon, the evolution of percutaneous coronary intervention (PCI) techniques and the improvement of both stent technology and antithrombotic treatment have led to a debate on the roles that PCI and coronary artery bypass graft (CABG) should play in the treatment of LMCA lesions [ 2 ]. Recently, several randomized controlled trials (RCT) and subsequent patient- and study-level meta-analyses have demonstrated an equipoise between PCI and CABG in a selected, low-risk subgroup of patients in terms of all-cause and cardiovascular mortality, major adverse cardiac events, myocardial infarction and stroke, albeit with a higher rate of subsequent revascularization with PCI [ 3 , 4 ]. Deciding between PCI and CABG is essentially based on the patients’ comorbidities, particularly diabetes mellitus, the surgical risk as assessed by the STS score or the EuroSCORE II, left ventricular ejection fraction (LVEF), the anatomical complexity assessed by the SYNTAX score and the need for concomitant valvular or aortic surgery [ 4 ].…”
mentioning
confidence: 99%